Colored food emulsions - implications of pigment addition on the rheological behavior and microstructure - Sousa, Isabel (2010)
Coloring foods with natural pigments enables the development of attractive products with nutritional advantages. The overall objective of this work was to study the consequences of adding the pigments lutein (lipophylic) and phycocyanin (hydrophilic) on the rheological behavior of oil-in-water food emulsions stabilized by pea protein isolate. The emulsions were characterized in terms of their linear viscoelasticity, and of their steady and transient flow behaviors. The rheological tests were monitored by using a microscope (optical analysis system) coupled to a con- trolled stress rheometer. Upon lutein incorporation, the emulsions became less stable, presenting lower rheological function values than the control emulsion (without pigment addition). On the other hand, phycocianin addition resulted in a significant reinforcement of emulsion structure, a higher resistance to structural breakdown becoming evident. An emulsion containing both pigments, in the same proportion, presented an intermediate rheological behavior resulting from a combination of the effects observed for the emulsions containing each of them.